2020
DOI: 10.21203/rs.2.24761/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of coronary collateralization on long-term clinical outcomes in type 2 diabetic patients after successful recanalization of chronic total occlusion

Abstract: Background: To assess the prognostic role of coronary collaterals in patients with type 2 diabetes mellitus (T2DM) after successful percutaneous coronary intervention (PCI) for chronic total occlusion (CTO). Methods: Coronary collateralization was graded according to Rentrop scoring system in 198 type 2 diabetic patients and 335 non-diabetics with stable angina undergoing PCI for at least one CTO lesion. Left ventricular ejection fraction (LVEF) was determined and major adverse cardio-cerebral events (MACCE) w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…First, patients in DM group were more likely to have complex clinical characteristics, like lower LVEF, which had a detrimental effect on cardiac function [10,14]. Second, DM, as a greater risk factor for adverse cardiovascular outcomes, alters glucose and lipid metabolism and in uences vascular endothelial function and angiogenesis [28,29,33]. Third, poor collateral circulation and microcirculation in diabetic patients may also partially account for the worse long-term prognosis, compared with non-diabetic patients [31,33,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, patients in DM group were more likely to have complex clinical characteristics, like lower LVEF, which had a detrimental effect on cardiac function [10,14]. Second, DM, as a greater risk factor for adverse cardiovascular outcomes, alters glucose and lipid metabolism and in uences vascular endothelial function and angiogenesis [28,29,33]. Third, poor collateral circulation and microcirculation in diabetic patients may also partially account for the worse long-term prognosis, compared with non-diabetic patients [31,33,36].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that DM patients with successful CTO-PCI were more likely to have lower LVEF, which may be related to poor coronary collateral circulation. However, recently, Yang et al reported that after successful recanalization of CTO, there was no signi cant distinction between diabetic and non-diabetic effects of coronary collaterals on MACCE and repeat revascularization during a median follow-up of 13.5 months[33]. Yang and co-workers speculated that well-developed coronary collaterals may not adequately substitute normal blood supply and thus good collateral circulation is insu cient.Recently, with regard to the long-term clinical outcomes of successful CTO-PCI in patients with versus without DM, a meta-analysis by Zhu et al which included 9847 patients after successful CTO-PCI (4238 diabetic patients and 5069 non-diabetic patients) revealed that the prevalence of MACEs (RR 1.26, 95% CI 1.02-1.56, P = 0.03) was signi cantly higher, compared with patients without DM[34].…”
mentioning
confidence: 99%